Study on the efficacy of TCM treatment in eczema patients with damp-heat syndrome - Woon, Ting Hui (2015)
Eczema is a chronic skin disease with complex immune mechanisms. This study aims to investigate the efficacy of TCM treatment in eczema patients, and the effect of additional cupping treatment in increasing recovery rates. Ten participants diagnosed with the TCM syndrome of damp-heat were included in this study, with five receiving TCM herbal medication and five receiving TCM herbal medication with cupping at the Shenque acupoint. Assessment of the participants took place during enrolment, at the third week after intervention and at the sixth week after intervention. Participants were assessed using the Severity Scoring of Atopic Dermatitis (SCORAD) as the primary outcome measure and Dermatology Life Quality Index (DLQI) as the secondary outcome measure. Results showed that TCM treatment may be effective in AD the treatment of eczema as there was an overall decrease in SCORAD and DLQI scores among all participants. However, there was no strong evidence that cupping increases treatment efficacy. Further investigations are required for a definite result, due to the limitations of this study.